Processing technology of glass fiber reinforced polyurethane energy-saving window frame profile

By adopting a three-stage temperature-controlled pultrusion equipment and impregnation tank design, combining continuous glass fiber and chopped glass fiber, and filling with silicon micropowder and hollow glass microbeads, the uniform performance in the existing glass fiber reinforced polyurethane profile production process is solved. The problems of poor performance, low production efficiency and high energy consumption have achieved efficient molding and excellent performance of profiles.

CN119489575APending Publication Date: 2025-02-21SICHUAN ZHOUYU HUAZHOU ARCHITECTURAL DESIGN CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411778998.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

The existing production process of glass fiber reinforced polyurethane profiles has problems such as poor performance uniformity, low production efficiency and high energy consumption.

Method used

The three-stage temperature-controlled pultrusion equipment and impregnation tank design are adopted, combined with the combination of continuous glass fiber and chopped glass fiber, and filled with silicon micropowder and hollow glass microbeads. The high-efficiency molding of the profile is achieved through efficient stirring and uniformly impregnation of the resin.

Benefits of technology

It significantly improves the thermal and mechanical properties of the profile, improves production efficiency, and ensures the performance consistency and energy-saving effect of the profile.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119489575A_ABST
    Figure CN119489575A_ABST
Patent Text Reader

Abstract

The invention discloses a glass fiber reinforced polyurethane energy-saving window frame profile processing technology which comprises the following steps: mixing and stirring polyether polyol, silica powder and hollow glass beads, and adding a catalyst and isocyanate; the continuous glass fibers are arranged through a yarn guide frame, impregnated with resin and adhered to the chopped glass fibers to enter a mold preforming area, forming is conducted through pultrusion equipment, and the profile is cut and sprayed after being cooled. According to the invention, high strength, low thermal conductivity and excellent stability of the profile are realized through optimized process parameters, and the profile is suitable for large-scale production of energy-saving window frames of buildings.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a door and window profile, and in particular to a processing technology of a glass fiber reinforced polyurethane energy-saving window frame profile. Background Art

[0002] As the requirements for building energy conservation continue to increase, traditional window frame materials (such as aluminum alloy and PVC) have gradually exposed problems such as high thermal conductivity and insufficient mechanical properties. Glass fiber reinforced polyurethane composites (GFRP) have become an ideal material in the field of energy-saving window frames because of their high strength, low thermal conductivity and corrosion resistance.

[0003] The existing glass fiber reinforced polyurethane profile production process has the following shortcomings:

[0004] Poor performance uniformity: The interface between glass fiber and polyurethane matrix is ​​not stable enough, which affects the mechanical properties.

[0005] Low production efficiency: Lack of process optimization design affects production capacity and economy.

[0006] High energy consumption: Cooling and heating processes are time-consuming and inefficient. Summary of the invention

[0007] The purpose of the invention is to provide a glass fiber reinforced polyurethane energy-saving window frame profile processing technology.

[0008] To achieve the above object, the present invention is implemented according to the following technical solutions:

[0009] The present invention comprises the following steps:

[0010] S1: prepare polyether polyol, isocyanate, continuous glass fiber, chopped glass fiber, silica powder, dibutyltin dilaurate, and hollow glass microspheres for use;

[0011] S2: Mix the polyether polyol, silica powder and hollow glass microspheres and stir them evenly, then add dibutyltin dilaurate and continue stirring, then add isocyanate and keep stirring at a low speed;

[0012] S3: The pultrusion equipment is preset with three-stage temperature control, which is divided into a preforming section, a reaction section and a cooling section, and the temperature of the reaction section is higher than the temperature of the preforming section;

[0013] S4: The continuous glass fibers are guided by a yarn guide frame and evenly distributed according to the cross-sectional design requirements. The continuous glass fibers are impregnated with the resin in step S2 through an impregnation tank. The impregnated continuous glass fibers evenly adhere to the chopped glass fibers and then enter the preforming area of ​​the mold. The resin evenly covers the fibers through the flow channel in the mold, and then enter the pultrusion equipment for pultrusion molding.

[0014] S5: The extruded profile passes through a cooling section, where the temperature is lowered to room temperature by air cooling or water cooling, the profile is cut according to the designed size, and the profile surface is polished;

[0015] S6: The polished profile surface is sprayed or coated to obtain a glass fiber reinforced polyurethane energy-saving window frame profile.

[0016] The beneficial effects of the present invention are:

[0017] The present invention is a glass fiber reinforced polyurethane energy-saving window frame profile processing technology. Compared with the prior art, the present invention has the following advantages:

[0018] Improved thermal performance: The filling of hollow microspheres significantly reduces the thermal conductivity of the material and improves the energy-saving effect of the profile.

[0019] Excellent mechanical properties: The combination of continuous and chopped glass fibers enhances the overall strength of the material while optimizing fracture toughness.

[0020] High process efficiency: Through the three-stage temperature control and dipping tank design, the heating and curing time are reduced and the production efficiency is improved.

[0021] Good production stability: precise control of process parameters ensures the consistency of profile size and performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 It is a process flow chart of the present invention. DETAILED DESCRIPTION

[0023] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments. The illustrative embodiments and descriptions of the present invention are used to explain the present invention but are not intended to limit the present invention.

[0024] like Figure 1 As shown: The present invention comprises the following steps:

[0025] S1: Prepare polyether polyol, isocyanate, continuous glass fiber, chopped glass fiber, silica powder, dibutyltin dilaurate, and hollow glass microspheres for use; by weight, it contains 35 parts of polyether polyol, 35 parts of isocyanate, 25 parts of continuous glass fiber, 5 parts of chopped glass fiber, 3 parts of silica powder, 1.5 parts of dibutyltin dilaurate, and 8 parts of hollow glass microspheres. The continuous glass fiber has a single filament diameter of 12 μm, the single filament diameter of the chopped glass fiber is 12 μm, and the length is 5 to 8 mm; the hollow glass microsphere has a particle size of 20 to 50 μm.

[0026] S2: The polyether polyol, silica powder and hollow glass microspheres are mixed and stirred evenly, and then dibutyltin dilaurate is added and stirring is continued, and then isocyanate is added and stirring is maintained at a low speed; the stirring speed is 300 rpm and the time is 10 minutes.

[0027] S3: The pultrusion equipment is preset with three temperature control sections, which are divided into a preforming section, a reaction section and a cooling section. The temperature of the preforming section is 50°C-70°C, the temperature of the reaction section is 80°C-150°C, and the temperature of the reaction section is higher than that of the preforming section.

[0028] S4: The continuous glass fiber is guided by a yarn guide frame and evenly distributed according to the cross-sectional design requirements. The resin of step S2 is impregnated through an impregnation tank. The impregnated continuous glass fiber evenly adheres to the chopped glass fiber and enters the preforming area of ​​the mold. The resin is evenly covered with the fiber through the flow channel in the mold, and then enters the pultrusion equipment for pultrusion molding; the resin temperature in the impregnation tank is maintained at 40°C-50°C, the stirring speed is controlled at 200rpm, and the traction speed is 10-15cm / min; the mold surface is evenly coated with a release agent and preheated to 50°C before processing.

[0029] S5: The extruded profile passes through the cooling section, where the temperature is lowered to room temperature by air cooling or water cooling. The cooling time is about 30-60 seconds. The profile is cut according to the designed size and the surface of the profile is polished.

[0030] S6: The polished profile surface is sprayed or coated to obtain a glass fiber reinforced polyurethane energy-saving window frame profile.

[0031] Resin mixing and impregnation principle: During the resin mixing stage, efficient stirring is used to ensure that the polyurethane matrix, silica powder and hollow glass beads are evenly distributed. The resin maintains appropriate temperature and viscosity in the impregnation tank to ensure that the continuous glass fiber and chopped glass fiber can be fully impregnated.

[0032] Mould forming and curing mechanism:

[0033] The zoned temperature control in the mold realizes the progressive reaction of the resin: the low temperature area in the preforming section ensures the arrangement and initial forming of the glass fiber bundles; the high temperature environment in the reaction section accelerates the curing reaction of the polyurethane, so that the profile has sufficient strength during the pultrusion process.

[0034] Improved mechanical properties: Continuous glass fiber enhances overall tensile and bending strength, while chopped glass fiber improves local impact resistance. Silica powder filling increases the rigidity of the composite material, while hollow glass microspheres reduce density and thermal conductivity.

[0035] Optimized energy saving: Hollow glass microspheres form a thermal resistance barrier in the matrix, significantly reducing the thermal conductivity, thereby improving the energy saving effect of the window frame profile.

[0036] Example 1: High-strength profile

[0037] Raw material ratio: polyether polyol: 35 parts, isocyanate: 35 parts, continuous glass fiber: 25 parts, chopped glass fiber: 5 parts, silica powder: 3 parts, dibutyltin dilaurate: 1.5 parts, hollow glass microspheres: 8 parts;

[0038] Process parameters: Impregnation tank resin temperature: 40°C, mold preforming section temperature: 60°C, mold reaction section temperature: 120°C, cooling section water temperature: 25°C

[0039] Example 2: High thermal insulation performance profile

[0040] Raw material ratio: polyether polyol: 33 parts, isocyanate: 33 parts, continuous glass fiber: 20 parts, chopped glass fiber: 7 parts, silica powder: 2 parts, dibutyltin dilaurate: 2 parts, hollow glass microspheres: 10 parts;

[0041] Process parameters: Impregnation tank resin temperature: 45°C, mold preforming section temperature: 55°C, mold reaction section temperature: 140°C, cooling section water temperature: 20°C

[0042] Example 3: Comprehensive performance profile

[0043] Raw material ratio: polyether polyol: 34 parts, isocyanate: 34 parts, continuous glass fiber: 22 parts, chopped glass fiber: 6 parts, silica powder: 4 parts, dibutyltin dilaurate: 1.8 parts, hollow glass microspheres: 8 parts

[0044] Process parameters:

[0045] Dipping tank resin temperature: 42°C, mold preforming section temperature: 58°C, mold reaction section temperature: 130°C, cooling section water temperature: 22°C;

[0046] The processes of the above-mentioned embodiments 1-3 are all in accordance with the process of the present invention, except that the parameters and proportions are different. The following is a comparison of the parameters of the above-mentioned embodiments 1-3:

[0047]

[0048] The experimental data table comprehensively compares the key performance indicators (tensile strength, flexural strength, thermal conductivity, product density) of the three embodiments and the comparative scheme. The following is a specific analysis and description of the data:

[0049] Tensile strength and bending strength: reflect the mechanical properties of the material. High tensile strength and bending strength indicate that the material can withstand greater tensile force and bending stress, and is suitable for use in high-strength window frame structures.

[0050] Thermal conductivity: represents the thermal insulation performance of the material. The lower the value, the worse the thermal conductivity of the material, the better the thermal insulation effect, and the more suitable it is for energy-saving window frames.

[0051] Product density: Indicates the lightweight degree of the material. Low density helps to reduce the overall weight of the window frame and is suitable for lightweight building materials.

[0052] Example 1 (High-strength profile)

[0053] Tensile strength: 160 MPa; Flexural strength: 240 MPa; The highest mechanical properties are shown, indicating that this embodiment enhances the overall structural strength of the material by using a higher proportion of continuous glass fiber and chopped glass fiber.

[0054] Thermal conductivity: 0.25W / m·K; Density: 1.8g / cm 3 ; It has low thermal conductivity and excellent thermal insulation performance, but slightly higher density, making it suitable for applications with higher requirements for mechanical properties.

[0055] Example 2 (High thermal insulation performance profile)

[0056] Tensile strength: 140MPa; Flexural strength: 200MPa; Mechanical properties are slightly lower than those of Example 1, but still higher than those of the comparative solution, meeting the load-bearing requirements of most window frames. Thermal conductivity: 0.18W / m·K; Density: 1.7g / cm 3 ; It has the best thermal insulation performance and the lowest density, and is suitable for scenarios with high requirements for energy saving and lightweight, such as passive buildings.

[0057] Example 3 (comprehensive performance profile)

[0058] Tensile strength: 150MPa; Flexural strength: 220MPa; Mechanical properties are between Example 1 and Example 2, with good overall performance. Thermal conductivity: 0.20W / m·K; Density: 1.75g / cm 3 ; It has both excellent thermal insulation performance and lightweight characteristics, suitable for ordinary energy-saving window frame needs.

[0059] Comparative solution (traditional materials)

[0060] Tensile strength: 120MPa; Flexural strength: 180MPa; The lowest mechanical properties, indicating that its stress resistance is limited and not suitable for the high strength requirements of modern buildings. Thermal conductivity: 0.35W / m·K; Density: 2.0g / cm 3 ; The thermal conductivity is relatively high, the thermal insulation performance is poor, and the density is large, which affects the overall lightweight.

[0061] in conclusion:

[0062] High strength requirement: Example 1; If the engineering requirements focus on mechanical properties (such as large window frames or high wind load areas), Example 1 is the best choice to ensure that the window frame has sufficient load-bearing capacity and rigidity.

[0063] High insulation requirements: Example 2; If the project focuses more on energy saving and lightweight (such as passive houses or ultra-low energy buildings), Example 2 wins with the lowest thermal conductivity and lightweight design.

[0064] Comprehensive performance: Example 3; For most general energy-saving window frame applications, Example 3 achieves a good balance between mechanical properties and thermal properties, and has an outstanding cost-effectiveness.

[0065] This data and analysis show that the process proposed in the present invention has significant performance advantages over traditional materials and provides a variety of optimization directions to meet the needs of different application scenarios.

[0066] The technical solution of the present invention is not limited to the above-mentioned specific embodiments. All technical variations made according to the technical solution of the present invention fall within the protection scope of the present invention.

Claims

1. A glass fiber reinforced polyurethane energy-saving window frame profile processing technology, characterized in that: The following steps are involved: S1: prepare polyether polyol, isocyanate, continuous glass fiber, chopped glass fiber, silica powder, dibutyltin dilaurate, and hollow glass microspheres for use; S2: Mix the polyether polyol, silica powder and hollow glass microspheres and stir them evenly, then add dibutyltin dilaurate and continue stirring, then add isocyanate and keep stirring at a low speed; S3: The pultrusion equipment is preset with three-stage temperature control, which is divided into a preforming section, a reaction section and a cooling section, and the temperature of the reaction section is higher than the temperature of the preforming section; S4: The continuous glass fibers are guided by a yarn guide frame and evenly distributed according to the cross-sectional design requirements. The continuous glass fibers are impregnated with the resin in step S2 through an impregnation tank. The impregnated continuous glass fibers evenly adhere to the chopped glass fibers and then enter the preforming area of ​​the mold. The resin evenly covers the fibers through the flow channel in the mold, and then enter the pultrusion equipment for pultrusion molding. S5: The extruded profile passes through a cooling section, where the temperature is lowered to room temperature by air cooling or water cooling, the profile is cut according to the designed size, and the profile surface is polished; S6: The polished profile surface is sprayed or coated to obtain a glass fiber reinforced polyurethane energy-saving window frame profile.

2. The glass fiber reinforced polyurethane energy-saving window frame profile processing process according to claim 1 is characterized in that: In the step S1, by weight, 35 parts of polyether polyol, 35 parts of isocyanate, 25 parts of continuous glass fiber, 5 parts of chopped glass fiber, 3 parts of silica powder, 1.5 parts of dibutyltin dilaurate, and 8 parts of hollow glass microspheres are contained.

3. The glass fiber reinforced polyurethane energy-saving window frame profile processing process according to claim 2 is characterized in that: The continuous glass fiber monofilament has a diameter of 12 μm, the short-cut glass fiber monofilament has a diameter of 12 μm, and a length of 5 to 8 mm; and the hollow glass microbead has a particle size of 20 to 50 μm.

4. The glass fiber reinforced polyurethane energy-saving window frame profile processing process according to claim 1, characterized in that: The stirring speed in step S2 is 300 rpm and the time is 10 minutes.

5. The glass fiber reinforced polyurethane energy-saving window frame profile processing process according to claim 1, characterized in that: In step S3, the temperature of the preforming section of the pultrusion equipment is 50°C-70°C, and the temperature of the reaction section is 80°C-150°C.

6. The glass fiber reinforced polyurethane energy-saving window frame profile processing process according to claim 1, characterized in that: In step S4, the resin temperature of the impregnation tank is maintained at 40°C-50°C, the stirring speed is controlled at 200rpm, and the pulling speed is 10-15cm / min; the mold surface is evenly coated with a release agent and preheated to 50°C before processing.